Evaluation of the Combined Administration of Chlorella fusca and Vibrio proteolyticus in Diets for Chelon labrosus: Effects on Growth, Metabolism, and Digestive Functionality - García-Márquez, Jorge; Vizcaino, Antonio Jesús; Barany, André; Galafat, Alba; Acién-Fernández, Francisco Gabriel; López-Figueroa, Félix; Alarcón López, Francisco Javier; Mancera Romero, Juan Miguel; Martos-Sitcha, Juan Antonio; Arijo-Andrade, Salvador; Abdala-Díaz, Roberto Teófilo (MDPI, 2023)
This study aimed to evaluate the combined effect of dietary Chlorella fusca and ethanol-inactivated Vibrio proteolyticus DCF12.2 (C + V diet) in Chelon labrosus juveniles, highlighting their nutritional, physiological, and morphological effects. The results showed that the combined dietary inclusion of C. fusca and V. proteolyticus significantly enhanced growth performance and feed utilization compared to the control group. The C + V diet increased the fish lipid quality index (FLQ), n-3 polyunsaturated fatty acids, and n-3/n-6 ratio, which might be beneficial in terms of human nutrition. The C + V diet considerably increased carbohydrate metabolic activity by statistically boosting plasma glucose. The dietary inclusion of C. fusca in conjunction with V. proteolyticus increased metabolic enzyme activity as well as intestinal absorption capacity compared to that found in the control group. In conclusion, the experimental diet was suitable for feeding C. labrosus, increasing their growth and the nutritional characteristics of the muscle and intestine, without causing tissue damage.
Keywords: Peces - Alimentación; Piscicultura; Ácidos grasos; Mugilidae; Absorptive capacity; Aquafeed; Bacteria; Enzymatic activity; Fatty acids; Fish quality; Fatty acids; Microalgae; Probiotic